Gamification of Interaction of Energy and Economic Incentive in Household Environment as a Holiday Assignment of the 7th Standard Students - Mishra, Indula (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Science teaching does not always involve big Lab set up and high-tech apparatuses, however teaching learning process of science could be innovative-in approach by using simple low-cost experimental models. This study identifies gamification as a self-directed literacy model to establish stimulatory tasks thereby achieve enhanced learning and application-based adaptability of the learnt skill-set. Model for gamification comprised of five-step process: ―understanding the target student population and relevant context of topic to be taught‖, ―defining learning objectives‖, ―structuring the experience‖, ―identifying the resources‖, and ―applying gamification elements‖. Target student population in this study was middle school, 7th standard students and gamification task was auditing and reducing electricity bill. Students were explained about the section of the electricity bill comprehensively. Learning objectives were to identify how to lower the electricity bill by identifying areas of reduction of the bill. Students were asked to structure their learning by understanding the house environment and modifications that can aid in reducing the electricity charge. The resources suggested were taking off any gadgets that remain in the socket, insulating the windows and minimizing opening of doors, keeping temperature of air conditioning at a regular level. Students learnt the gamification elements of reducing the energy loss and conservation as the primary endpoint of this teaching/learning model. Students also learnt selection of key areas of improvement as an economic incentive and lastly, they integrated the concept of energy and economic incentive in their household environment.